(NeDINSTWO CELI(B. (Nw DOBRYJ PUTX(B, (NREBQTA(B! :s (NPOSOBIE DLQ U^ITELQ (B/s - (NaMONA[WILI(B, (N{ALWA aLEKSANDROWI^(B,s; (NmUHINA(B, (Nw(B. (Ns(B.s (ND(B-(NR PED(B. (NNAUK(B,s ((NmOSKWA (B:s (NpROSWE]ENIE(B,s, 1987)
(NaWTOR ]EDRO DELITSQ NAKOPLENNYM OPYTOM(B, (NPRIOB]AET K SWOIM PEDAGOGI^ESKIM IDEQM(B.s
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NpEDAGOG)QÆKAs)E -- (NwIHOWANNQs; (NPO^ATKOWA [KOLAs; (NKOLEKTIWs; (ND)QÆTIs)E